Answer:
[tex]h(x) = (x +3)(x^2+1)[/tex]
Step-by-step explanation:
The shape of the graphed polynomial function is an S-shaped curve, suggesting that it is a cubic function with a degree of 3.
The factored form of a cubic function can be expressed as:
[tex]h(x) = a(x - r_1)(x - r_2)(x - r_3)[/tex]
where:
- a is the leading coefficient.
- r₁, r₂ and r₃ are the zeros.
The real zeros of a function are the x-values where the graph of the function intersects or crosses the x-axis. As the graphed polynomial crosses the x-axis at x = -3, then one of the zeros is x = -3.
Given that the other zeros of the function are x = i and x = -i, the factored form of the graphed function h(x) is:
[tex]h(x) = a(x - (-3))(x - i)(x - (-i))[/tex]
[tex]h(x) = a(x +3)(x - i)(x+i)[/tex]
Expand the function:
[tex]h(x) = a(x +3)(x^2+xi-xi-i^2)[/tex]
[tex]h(x) = a(x +3)(x^2-(-1))[/tex]
[tex]h(x) = a(x +3)(x^2+1)[/tex]
To find the value of the leading coefficient, substitute the y-intercept (0, 3) into the function and solve for a:
[tex]\begin{aligned}a(0 +3)(0^2+1)&=3\\a(3)(1)&=3\\3a&=3\\a&=1\end{aligned}[/tex]
Therefore, the equation of the graphed polynomial function is:
[tex]\Large\boxed{\boxed{h(x) = (x +3)(x^2+1)}}[/tex]